Numerical estimation of a tsunami source at the flexural area of Kuril and Japan Trenches in the fifteenth to seventeenth century based on paleotsunami deposit distributions in northern Japan - Sato, Kai; Yamada, Masaki; Ishimura, Daisuke; Ishizawa, Takashi; Baba, Toshitaka (Progress in earth and planetary science, 2022)
Paleotsunami deposit investigations and numerical tsunami computations have been performed to elucidate the source and size of large tsunamis along the Kuril to Japan Trenches, particularly for unusual tsunamis that occurred in the seventeenth century, the 1611 CE Keicho tsunami (M 8.1) along the Japan Trench and seventeenth-century tsunami (> Mw 8.8) along the Kuril Trench, which caused serious damages on the coastal residents and environments. Moreover, several paleotsunami deposits dating from the thirteenth to eighteenth centuries have been reported along the area between the Kuril and Japan subduction zones, but their sources have not been clarified. In this study, we estimated the tsunami sources from numerical simulations using the distribution of fifteenth- to seventeenth-century tsunami deposits at Sekinehama along the coast of the Shimokita Peninsula. Based on numerical simulations with previously proposed fault models, the tsunami deposits showing similar ages at Sekinehama and another site on the coast of Shimokita Peninsula, which are within 50 km apart, could not be explained except with the huge earthquake models (> Mw 9.1), whose rupture zones extend to not only the Kuril or Japan Trenches but also their flexural area. Thus, we modified or newly proposed twelve fault models located in the flexural area between the two trenches to explain tsunami deposits possibly around the seventeenth century at the above-mentioned two sites on the coast of Shimokita Peninsula. Simulations using these models elucidated that the rupture in the shallow or deep plate boundaries with > 14–32 m slip (> Mw 8.55–8.76) is necessary. If the tsunami deposits around the seventeenth century along the Iburi–Hidaka coast in Hokkaido and those at the two sites mentioned above might be left by an identical event, an interplate earthquake with > 18–40 m slip (> Mw 8.62–9.2) in the flexural area is needed. Moreover, this interplate earthquake might have occurred in the deep plate boundary than in the shallower plate boundary based on slip deficit and slow earthquake distribution data. Our results offer significant insights into a large earthquake (> M 8) along the Kuril and Japan Trenches in the fifteenth to seventeenth century.